COMPARISON OF THE EFFECT OF ELECTROLYTE CHANGES ON ECGS OF PATIENTS PRESENTED IN EMERGENCY ROOM WITH RENAL FAILURE DURING PRE AND POST HAEMODIALYSIS AND THEIR CORRELATION. (Indian Journal of Applied-Basic Medical Sciences, 2020)
Introduction Cardiovascular disease is a most common reason for mortality and morbidity among patients on haemodialysis. It is responsible for up to 30% of sudden death among patients during and sometime after dialysis Methods In this prospective study, 76 patients were recruited; all patients with Age > 18 years of renal failure, and all patients providing consent and undergoing first-time haemodialysis treatment were included. The mean duration for sessions of the dialysis was around 3 hours. Patients with Known case of arrhythmias on antiarrhythmic drugs, Known case of IHD and Congenital long QT syndrome, Patients on drug that might have an effect on QT interval, Post CPR, Cardiac resynchronization therapy, Pacemaker, and an implantable cardioverter-defibrillator were excluded from the study.Results Out of 76 patients 46 were male and 30 were female. Atrial arrhythmias were seen more commonly than ventricular arrhythmias. 42 patients had pre-HD ECG changes; Out of them Sinus tachycardia was seen in 11 patients; 13 patients had atrial premature beats; 6 patients had ventricular premature contraction and 12 patients had ST-T changes were seen in ECG changes before HD. 12 patients without pre-HD ECG changes developed ECG changes post-HD. Total 23 patients had ECG changes after HD. Out of them Sinus tachycardia was seen in 10 patients;8 patients had atrial premature beats; 3 patients had ventricular premature contraction and 2 patients had ST-T changes were seen in ECG changes after HD. Conclusion There were significant changes in ECG parameters and serum electrolytes during haemodialysis. However, there was no obvious influence of serum K+ on the ECGs in a patient with renal failure, apart from the net change of serum K+ on the amplitude T wave difference, during haemodialysis. More evaluation with a larger sample to see the effect of electrolyte on ECG changes might be required. The prolonged QTc interval was weakly negative correlated with serum potassium. Post haemodialysis ECG would effectively identify patients whose repolarization substitute increase after dialysis sessions. In these individuals, a dialysis regimen can be selected which is rarely change ventricular repolarization.
Keywords: Cardiovascular disease; prospective study; IHD; QT; CPR